Exploring the Compliance Analysis and the Determinants of Quality of Integrated Reports : Evidence from India - Ara, Musarrat; B., Harani (Indian Journal of Research in Capital Markets, 2024)
The research looked into five research questions to determine the factors that determine report quality as well as the compliance of integrated reports of specific Indian companies reported for 2018–2019. Ninety-two questions in the compliance analysis index adhered to the <IR> framework, while the second index, intended for non-financial disclosures, contained 90 KPIs in accordance with the GRI criteria. For in-depth analysis, we rigorously reviewed the top 500 companies listed on NSE/BSE and finally came up with 32 reports for the year 2018–2019. The study revealed that the integrated reports complied with the <IR> framework, and the determinants that were significant and positively associated with the quality of integrated reports are firm size measured by revenue, assurance, and management dialog on IR. However, a negative association was found for the market capitalization with the quality of IR.